Characterization of total phenolic and flavonoid content in Pseudoconyza viscosa (Mill.) and its in-silico antioxidant evaluation - Zahid, Ayesha; Hussain, Abrar; Mehmood, Asim; Iqbal, Muhammad Adnan; Akram, Muhammad; Iqbal, Javaid; Seleiman, Mahmoud F.; Ali, Nawab; Al-Saif, Adel M. (Frontiers in Plant Science, 2025)
IntroductionThe Pseudoconyza viscosa (Mill.) is an important medicinal plant found in tropical and warm areas, and is known for its application in the food, cosmetic, and pharmaceutical industries. However, no information is available regarding its chemical composition, total phenolics and antioxidant potential. Thus, the present study aimed to investigate the total phenolic and flavonoid contents and their antioxidant potential through insilico studies.MethodsThe ethanolic extracts were characterized by high-pressure liquid chromatography (HPLC) and UV-visible spectroscopy. Seventeen peaks were detected based on UV- spectroscopy. Furthermore, molecular docking of major phenolic compounds was carried out using Autodock Vina Software against human peroxiredoxin 5 (PDB ID: 1HD2) to study its antioxidant potential. Further, ADME predictions were made to determine physiochemical characteristics of the lead compound.ResultsThe total phenolic and flavonoid contents of Pseudoconyza viscosa (Mill.) ethanolic extracts were 311.74 and 208.2 mg/g respectively. Molecular docking results showed that dicaffeoylquinic acid (docking score -7.8) has significant binding potential against human peroxiredoxin 5 (PDB ID: 1HD2). ADME and drug likeness parameters have also shown that dicaffeoylquinic acid can be used as a potential antioxidant candidate compared to synthetic antioxidant drugs with side effects.DiscussionThe results of this study underscore the therapeutic potential of Pseudoconyza viscosa (Mill.), warranting further investigation into its bioactive compounds for potential applications in pharmaceuticals and nutraceuticals. Future research should focus on exploring the mechanisms and efficacy of these compounds in clinical settings, paving the way for the development of novel therapeutic agents derived from this medicinal plant.